Komparasi Hasil Belajar Matematika pada Penggunaan Model Pembelajaran Quantum Learning Siswa Kelas IV di MIN 1 Ponorogo - Nur Hidayah; Kurnia Hidayati (Institut Agama Islam Negeri Ponorogo, 2022)
The learning model is a set of methods that influence learning so that it is active and conducive. Learning outcomes can experience significant fluctuations due to many factors, one of which is the learning model. The low mathematics results of fourth grade students at MIN 1 Ponorogo are caused by the lack of precise learning models applied. This study aims to (1) determine the mathematics learning outcomes of fourth grade students at MIN 1 Ponorogo using the quantum learning model; (2) knowing the mathematics learning outcomes of fourth grade students at MIN 1 Ponorogo who do not use the quantum learning model; (3) knowing the difference in the mathematics learning outcomes of fourth grade students at MIN 1 Ponorogo between those who use and do not use the quantum learning model. This type of research is quantitative with a posttest-only control-design. The research was carried out at MIN 1 Ponorogo class IV consisting of 48 students with 25 students in Al-Idris class as the experimental class and 23 students in Zaid bin Tsabit's class as the control class. The results of the research are (1) the mathematics learning outcomes of fourth grade students at MIN 1 Ponorogo who use the quantum learning learning model get an average score of 77 with a percentage of the high category value of 12%, the medium category of 76%, the low category of 12%, (2) The mathematics learning outcomes of fourth grade students at MIN 1 Ponorogo who do not use the quantum learning learning model get an average score of 63.78 with a percentage value of 22% in the high category, 56% in the medium category, and 22% in the low category. (3) There is a significant difference in the mathematics learning outcomes of fourth grade students of MIN 1 Ponorogo between those who use and do not use the quantum learning model